2018
DOI: 10.1002/dys.1607
|View full text |Cite
|
Sign up to set email alerts
|

It is the egg, not the chicken; dorsal visual deficits present in dyslexia are not present in illiterate adults

Abstract: Some individuals with dyslexia demonstrate deficits in reading, visual attention, and visual processing which can be attributed to a functional failure of the magnocells in the visual system or in the dorsal visual pathway. The study examines the role of magno/dorsal function in dyslexic adults compared with normal, illiterate, and semi‐literate readers. Coherent motion and coherent form were used in Experiment 1, and the frequency doubling illusion and static‐gratings were used in Experiment 2. If a magno/dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Pammer and Wheatley 14 verified that a group of 21 dyslexics had a poorer performance in detecting a visual stimulus selective of the magnocellular system, when compared to 19 readers of the control group (F (1.38) = 13.6, p< 0.001), with diminished sensibility in comparison with the standardized age cohort. In the study by Flint and Pammer 12 , illiterate adults obtained the same performance as that of normal and semi-illiterate readers in temporal and spatial tasks specific of the visual magnocellular system, and these three groups had a better performance than the group of dyslexic readers. The authors conclude 12 that this functional failure of the dorsal visual pathway in dyslexia is probably not a consequence of the lack of reading; they point to a causal role of the magnocellular processing, instead.…”
Section: Discussionmentioning
confidence: 77%
“…Pammer and Wheatley 14 verified that a group of 21 dyslexics had a poorer performance in detecting a visual stimulus selective of the magnocellular system, when compared to 19 readers of the control group (F (1.38) = 13.6, p< 0.001), with diminished sensibility in comparison with the standardized age cohort. In the study by Flint and Pammer 12 , illiterate adults obtained the same performance as that of normal and semi-illiterate readers in temporal and spatial tasks specific of the visual magnocellular system, and these three groups had a better performance than the group of dyslexic readers. The authors conclude 12 that this functional failure of the dorsal visual pathway in dyslexia is probably not a consequence of the lack of reading; they point to a causal role of the magnocellular processing, instead.…”
Section: Discussionmentioning
confidence: 77%
“…Pre-readers at risk of dyslexia show the same threshold differences to the FD illusion presented at 50 Hz ( Kevan and Pammer, 2008 ) and illiterate, semi-literate, and literate adults are all equally sensitive to the illusion presented at 50 Hz ( Flint and Pammer, 2011 ). This suggests that sensitivity to the FD illusion is not dependant on magnocellular development as a child learns to read and is therefore not a consequence of failing to learn to read ( Kevan and Pammer, 2008 ; Flint and Pammer, 2019 ). Furthermore, individual differences in sensitivity to the FD illusion are predictive of reading performance in dyslexic children ( Gori et al, 2014 ).…”
Section: Neurophysiological Theories and Evidence Pertinent To Readinmentioning
confidence: 95%
“…Previous research has usually adopted tasks of gap detection, temporal order judgement, coherent motion detection, and moving/flickering grating detection to measure low‐level visual temporal ability (Farmer & Klein, 1995; Flint & Pammer, 2018; McLean et al, 2011). Relevant studies in the contexts of different languages have found that children's performances in coherent motion detection, temporal order judgement, and moving grating detection were significantly correlated with word/sentence reading speed (Kevan & Pammer, 2008; Lawton, 2016; Lawton & Shelley‐Tremblay, 2017; Main et al, 2014; Van Zuijen et al, 2012; Zhao, Bi, & Coltheart, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies in the contexts of different languages have found that children's performances in coherent motion detection, temporal order judgement, and moving grating detection were significantly correlated with word/sentence reading speed (Kevan & Pammer, 2008; Lawton, 2016; Lawton & Shelley‐Tremblay, 2017; Main et al, 2014; Van Zuijen et al, 2012; Zhao, Bi, & Coltheart, 2017). Additionally, relevant studies showed that individuals with reading fluency difficulty had poorer behavioural performance in visual tasks of gap detection (Farmer & Klein, 1995), temporal order judgement (Farmer & Klein, 1995), and coherent motion detection (Conlon, Sanders, & Wright, 2009; Flint & Pammer, 2018; Meng, Cheng‐Lai, Zeng, Stein, & Zhou, 2011; Wright & Conlon, 2009) compared to age‐matched normal readers, revealing dysfunction in VTP for individuals with reading dysfluency. The above findings from group comparisons also revealed a close relationship between low‐level VTP skills and reading fluency (Lobier, Dubois, & Valdois, 2013; Lobier, Zoubrinetzky, & Valdois, 2012; Main et al, 2014; McLean et al, 2011).…”
Section: Introductionmentioning
confidence: 99%